في أصول الغزلية الأندلسية - عمارة بوبكرد.علي (Aljameai, 2023)
المستخلص: يتعلّق عملنا بالبحث في أصول الغزلية الأندلسية من خلال النّصوص الأندلسيّة الغزلية وهي عندنا تنقسم إلى نصين أولهما شعري ينظر في أحوال الجسد العفيف والاباحي، أما النص الثاني فيتعلق بجسد الموشّحات وقد بان لنا ان الغزلية في الاندلس لها اصول مشرقية ولها كذلك بتربة الاندلس وهوائها امشاج فهو ندي غضّ. SummaryOur work is related to researching the origins of the Andalusian ghazal through the Andalusian ghazal texts, which we have divided into two texts. As for the second text, it relates to the body of muwashshahs It has become clear to us that the ghazalism in Andalusia has oriental origins, and it also has the soil of Andalusia, and its air is mixed, as it is a juicy dew.